Evolution Characteristics of Land Use Transformation and Its Impact on Ecological Security in Baotou City During 2001-2020 - Xue Jianchun; Cao Libo (Shuitu baochi tongbao)
[Objective] The relationship between land use transformation and ecological security in Baotou City, Inner Mongolia Autonomous Region was analyzed from the perspectives of land use quantity transformation and social and economic comprehensive evaluation in order to provide a basis for building an ecological barrier area in Northern Xinjiang Uygur Autonomous Region. [Methods] Land use transfer of Baotou City during 2001—2020 was analyzed by using the information Atlas method of ArcGIS. The land ecological security, the dominant transfer index, and the invisible transfer index were calculated by using the comprehensive evaluation method. The coordinated development relationship was explored using the coupling coordination analysis model. The causal relationship was analyzed by using the econometric statistical method. [Results] ① The expansion of construction land was mainly based on the consumption of cultivated land during the study period, with a total of 489.91 km2 of new construction land, 503.84 km2 of new reduced cultivated land, and 84.43 km2 of new grassland; ② The land ecological security in Baotou City had improved during the research period, and it was in the running stage and high-level coupling stage with land use transformation. The coupling degree between dominant transformation and ecological security was greater than the coupling degree between recessive transformation and ecological security; ③ The dominant transfer of land use had a negative impact on land ecological security, while the recessive transfer of land use had a positive impact on land ecological security. [Conclusion] The planners should not only pay attention to the quantity of land use transformation in Baotou City, but also pay more attention to the efficient use of the transformed land, improving the efficiency of land use, and ensuring the optimization of stock and the flow of land efficiency.